2020
DOI: 10.3390/ma13071694
|View full text |Cite
|
Sign up to set email alerts
|

Application of Magnetic Resonance Techniques to the In Situ Characterization of Li-Ion Batteries: A Review

Abstract: In situ magnetic resonance (MR) techniques, such as nuclear MR and MR imaging, have recently gained significant attention in the battery community because of their ability to provide real-time quantitative information regarding material chemistry, ion distribution, mass transport, and microstructure formation inside an operating electrochemical cell. MR techniques are non-invasive and non-destructive, and they can be applied to both liquid and solid (crystalline, disordered, or amorphous) samples. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 84 publications
0
11
0
1
Order By: Relevance
“…Polarization experiments (galvanostatic, 1.96 mA cm –2 for 7344 s) were performed with a Zahner Zennium Pro workstation. Based on MRI cell designs from the literature, ,,, a homemade 3D-printed PLA cell was used for operando measurements, exploiting 500 μm roll-pressed lithium metal foils as electrodes. Because of an interelectrode distance of 7.5 mm, 48 FS 2190 separators fully soaked with electrolyte prior to cell assembly were used, in this way affording a homogeneous electrolyte distribution between the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Polarization experiments (galvanostatic, 1.96 mA cm –2 for 7344 s) were performed with a Zahner Zennium Pro workstation. Based on MRI cell designs from the literature, ,,, a homemade 3D-printed PLA cell was used for operando measurements, exploiting 500 μm roll-pressed lithium metal foils as electrodes. Because of an interelectrode distance of 7.5 mm, 48 FS 2190 separators fully soaked with electrolyte prior to cell assembly were used, in this way affording a homogeneous electrolyte distribution between the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Famprikis et al [51] and Zhang et al [116] reported on the fundamentals of electrolytes and Oudenhoven et al [117], Julien and Mauger [60], and Rambabu et al [118] reviewed the technology of solid-state microbatteries. Moreover, in situ and ex situ techniques were explored for elucidating the solid electrode/electrolyte interfaces [40,67,80,98,[119][120][121][122][123] and computational methods were reviewed by Xiao et al [94] for understanding the conduction mechanisms in both oxide and sulfide electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Here, in situ studies during battery cycling are vitally important. [130][131][132][133][134][135][136][137][138][139] For instance, in situ XRD has been applied to monitor the phase transitions of electrode materials during battery cycling and should be used to obtain information on the structural evolution of LIG battery electrodes. [140] To conclude, LIG has many characteristics that make it a promising material for batteries, delivering 1) an increase in ionic diffusion, 2) a rise in active sites for mobile ion absorption, 3) accommodation of volume expansion, 4) suppression of dendrite formation of metal anodes, and 5) confinement of electrode dissolution.…”
Section: Discussionmentioning
confidence: 99%